Microbial community structural response to variations in physicochemical features of different aquifers - Dai, Heng; Zhang, Yiyu; Fang, Wen; Liu, Juan; Hong, Jun; Zou, Chaowang; Zhang, Jin (Frontiers in Microbiology, 2023)
The community structure of groundwater microorganisms has a significant impact on groundwater quality. However, the relationships between the microbial communities and environmental variables in groundwater of different recharge and disturbance types are not fully understood. In this study, measurements of groundwater physicochemical parameters and 16S rDNA high-throughput sequencing technology were used to assess the interactions between hydrogeochemical conditions and microbial diversity in Longkou coastal aquifer (LK), Cele arid zone aquifer (CL), and Wuhan riverside hyporheic zone aquifer (WH). Redundancy analysis indicated that the primary chemical parameters affecting the microbial community composition were NO3-, Cl-, and HCO3-. The species and quantity of microorganisms in the river–groundwater interaction area were considerably higher than those in areas with high salinity (Shannon: WH (6.28) > LK (4.11) > CL (3.96); Chao1: WH (4868) > CL (1510) > LK (1222)). Molecular ecological network analysis demonstrated that the change in microbial interactions caused by evaporation was less than that caused by seawater invasion under high-salinity conditions ((nodes, links): LK (71,192) > CL (51,198)), whereas the scale and nodes of the microbial network were greatly expanded under low-salinity conditions ((nodes, links): WH (279,694)). Microbial community analysis revealed that distinct differences existed in the classification levels of the different dominant microorganism species in the three aquifers. Environmental physical and chemical conditions selected the dominant species according to microbial functions. Gallionellaceae, which is associated with iron oxidation, dominated in the arid zones, while Rhodocyclaceae, which is related to denitrification, led in the coastal zones, and Desulfurivibrio, which is related to sulfur conversion, prevailed in the hyporheic zones. Therefore, dominant local bacterial communities can be used as indicators of local environmental conditions.